Show me to the tradesman's entrance : acatalogue published on the occasion of the 2004 Hiscox MFA Glasgow degree show - Tramway, Glasgow (Glasgow : Tramway Glasgow, 2004)
Andrews, Cynthia ; Barker, Ruth ; Beall, ts ; Black, Karla ; Dahlstrom, Audhild ; Delaney, April ; Dembroski, Benjamin ; Duke, William ; Edin, Edin, Linnéa Therese ; Eyres, Erica ; Hetherington, Iain ; Inoue, Hideko ; Krull, Barbara ; Nistrup, Ursula ; Phillips, Ciara ; Sigurdardóttir, Sigga Björg ; Stumpf, Michael ; Sulzer, Andrea ; Webster, Christine ; Yeo Chee Kiong
biog., tent. p. 55-61
Engels
Published on the occasion of the 2004 Hiscox MFA Glasgow degree show, at Tramway, Glasgow, 17.06.2004 - 27.06.2004
boek